A
using the Cosine rule in ΔSTU
let t = SU, s = TU and u = ST, then
t² = u² + s² - (2us cos T )
substitute the appropriate values into the formula
t² = 5² + 9² - (2 × 5 × 9 × cos68° )
= 25 + 81 - 90cos68°
= 106 - 33.71 = 72.29
⇒ t =
≈ 8.5 in → A
Answer:
The answer is B.
Step-by-step explanation:
The original graph of y = x^2 has a vertex at (0,0)
The formula for graph translations is y = (x-#)^2+#
The number inside the parentheses is a horizontal translation.
So, we are given y = (x-(-3))^2+#
The vertex of the graph moves 3 points left, since the number is negative (-3).
The number at the end of the equation is a vertical translation.
So, we are given y = (x+3)^2+4
The vertex of the graph moves 4 points up, since the number is positive (4).
The new vertex is at (-3,4)
Answer:
265.2
Step-by-step explanation:
3(6*13)=234
2*15.6=31.2
234+31.2=265.2
0.1 0.2 because its only sum of only 0.3